Review article: the pathogenesis of pouchitis. Issue 8 (24th August 2016) - Schieffer, K. M.; Williams, E. D.; Yochum, G. S.; Koltun, W. A.
Summary: Background: A total proctocolectomy followed by ileal pouch‐anal anastomosis is a potentially curative surgery for ulcerative colitis or familial adenomatous polyposis. About 5–35% of patients with ulcerative colitis and 0–11% of patients with familial adenomatous polyposis develop subsequent inflammation of the ileal pouch termed pouchitis. Aim: To provide a comprehensive analysis of the research studying the possible pathogenesis of pouchitis. The goals were to identify promising areas of investigation, to help focus clinicians, researchers and patients on how to better understand and then potentially manage ileal pouchitis, and to provide avenues for future research investigations. Methods: This review examined manuscripts from 1981 to 2015 that discussed and/or proposed hypotheses with supportive evidence for the potential underlying pathogenic mechanism for pouchitis. Results: The pathogenesis of pouchitis is not definitively understood, but various hypotheses have been proposed, including (i) recurrence of ulcerative colitis, (ii) dysbiosis of the ileal pouch microbiota, (iii) deprivation of nutritional short‐chain fatty acids, (iv) mucosal ischaemia and oxygen‐free radical injury, (v) host genetic susceptibility and (vi) immune dysregulation. However, none of these alone are able to fully explain pouchitis pathogenesis. Conclusions: Pouchitis, similar to inflammatory bowel disease, is a complex disorder that is not caused by any one single factor. More likely, pouchitis occurs through a combination of both dysregulated host inflammatory mechanisms and interaction with luminal microbiota.